Activation of STING Pathway Contributed to Cisplatin-Induced Cardiac Dysfunction via Promoting the Activation of TNF-α-AP-1 Signal Pathway - Wang, Lintao; Zhang, Suya; Han, Jibo; Nie, Xiaoyan; Qi, Yajun; Han, Yingying; Chen, Xiong; He, Chaoyong (Frontiers in Pharmacology, 2021)
Cardiovascular complications are a well-documented limitation of conventional cancer chemotherapy. As a notable side effect of cisplatin, cardiotoxicity represents a major obstacle to the treatment of cancer. Recently, it has been reported that cyclic GMP-AMP synthase (cGAS)- stimulator of interferon genes (STING) signaling pathway was associated with the occurrence and development of cardiovascular diseases. However, the effect of STING on cardiac damage caused by cisplatin remains unclear. In this study, cisplatin was shown to activate the cGAS-STING signaling pathway, and deficiency of STING attenuated cisplatin-induced cardiotoxicity in vivo and in vitro. Mechanistically, the STING-TNF-α-AP-1 axis contributed to cisplatin-induced cardiotoxicity by triggering cardiomyocyte apoptosis. In conclusion, our results indicated that STING might be a critical regulator of cisplatin-induced cardiotoxicity and be considered as a potential therapeutic target for preventing the progression of chemotherapy-associated cardiovascular complications.